2021
DOI: 10.3390/agronomy11020228
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Deficit Irrigation and Reduced N Fertilization on Plant Growth, Root Morphology and Water Use Efficiency of Tomato Grown in Soilless Culture

Abstract: This study was conducted to investigate the effects of various irrigation water (W) and nitrogen (N) levels on growth, root-shoot morphology, yield, and irrigation water use efficiency of greenhouse tomatoes in spring–summer and fall–winter. The experiment consisted of three irrigation water levels (W: 100% of crop evapotranspiration (ETc), 80%, and 60% of full irrigation) and three N application levels (N: 100%, 75%, and 50% of the standard nitrogen concentration in Hoagland’s solution treatments equivalent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…Ma et al [37] also concluded that the total root number of grapevines significantly decreased by about 55% from high to low irrigation rates under subsurface drip irrigation. Similar results have been reported by Gao et al [38], Ahmed et al [39], and Ullah et al [40]. In this study, although the fine root growth was inhibited by the water stress applied during Stage 1, significant differences in RLD were only observed between SRDI-1 and control treatments in May of 2010.…”
Section: Fine Root Distribution In the Irrigated Zone Affected By Rdisupporting
confidence: 91%
“…Ma et al [37] also concluded that the total root number of grapevines significantly decreased by about 55% from high to low irrigation rates under subsurface drip irrigation. Similar results have been reported by Gao et al [38], Ahmed et al [39], and Ullah et al [40]. In this study, although the fine root growth was inhibited by the water stress applied during Stage 1, significant differences in RLD were only observed between SRDI-1 and control treatments in May of 2010.…”
Section: Fine Root Distribution In the Irrigated Zone Affected By Rdisupporting
confidence: 91%
“…This decline in yield is linked to sub-optimal crop management, which could include poor fertilization and irrigation, and to abiotic constraints (pedoclimatic variations, land degradation, etc.) (Ferrante and Mariani, 2018;Ullah et al, 2021). The fundamental cause is the degradation of land followed by their loss of fertility (physical, chemical, and biological fertility).…”
Section: Introductionmentioning
confidence: 99%
“…68,69 They examined that coupling optimal moisture conditions with fertilizer level can promote root growth, allowing plants to receive more nutrients from the soil, resulting in better plant growth and development. 70 Under an open field, deficit watering with the optimal amount of fertilizer has been identified as a beneficial strategy for water 71 and fertilizer conservation at small farms in irrigated areas of Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing irrigation water and nitrogen level from a specified limit can negatively impact wheat yield and parameters. 71 As a result, the various interactions of deficit irrigation and reduced nitrogen rates can be examined in the broader context in the future. PCA is a widely used method in modern data analysis and for exploring the interaction between various factors.…”
Section: Discussionmentioning
confidence: 99%